Hands to the spindle : Texas women and home textile production, 1822-1880 - Marks, Paula Mitchell, 1951- (Clayton Wheat Williams Texas life series, 1996)
In nineteenth-century Texas women's hands often created the fabrics their families wore, the blankets used to cover their tired bodies, and the textiles that furnished their homes. Through spinning, weaving, dyeing, and knitting of clothing and linens, women displayed their abilities and their dreams of a better future. These day-to-day activities of Texas women spinners and weavers come to life in award-winning author Paula Mitchell Marks's Hands to the Spindle. The hum.